Results of 115 Rubis II reverse thumb carpometacarpal joint prostheses with a mean follow-up of 10 years. (July 2017) - Dehl, M.; Chelli, M.; Lippmann, S.; Benaissa, S.; Rotari, V.; Moughabghab, M.
The aim of this study was to assess the clinical and radiological results of the Rubis II thumb carpometacarpal joint reverse prosthesis, at a mean follow-up of 10 years. Between 1997 and 2008, 253 prostheses were implanted in 199 patients; 115 were reviewed. The survival after a mean of 10 years was 89%. At the last follow-up, 70% of prostheses were painless; the others reported moderate or intermittent pain. The satisfaction rate was 98%. The mean opposition was 9 on the Kapandji scale; the mean QuickDASH score was 30. Wrist, key and tip pinch strengths were comparable with the non-operated side. Of the 115 implants, one was radiologically loose (1%) and 15 had suffered dislocations (13%), 12 of which were caused by an injury. Eleven thumbs had revision surgery. This study confirms that the good clinical results of the Rubis II prosthesis are maintained in the medium and long term, and represents a useful alternative to trapeziectomy for selected patients. Level of evidence: IV